Experimental Study on the Three-Dimensional Unsteady Flow Characteristics of the Counter-Rotating Axial Flow Fan - Lee-Sang CHO; Bong-Jun CHA; Jin-Soo CHO (Journal of Fluid Science and Technology, 2009)
The counter-rotating axial flow fan shows that the complex flow characteristics with three-dimensional, viscous, and unsteady flow fields. For the understanding of the entire core flow in counter-rotating axial flow fan, it is necessary to investigate the three-dimensional unsteady flow field between the rotors. This information is also essential for the improvement of the aerodynamic characteristics, the reduction of the aerodynamic noise level and vibration characteristics of the counter-rotating axial flow fan. The purpose of this study is, therefore, to present the periodic characteristics of the blade passage flow, the wake and the tip vortex, which are utilized for the blade design data for the improvement of the aerodynamic characteristics, the reduction of the aerodynamic noise level and vibration characteristics of the counter-rotating axial flow fan. In this paper, the three-dimensional unsteady flow by the rotor-rotor interaction of the CRF were investigated at the design point(peak efficiency operating point). Unsteady flow fields in the CRF are measured at the cross-sectional planes of the upstream, between and downstream of each rotor using the 45° inclined hot-wire probe. The stationary hot-wire technique used the 45° inclined hot-wire probe, which rotates successively with 120 degrees increments about its own axis. And, the sampling data of unsteady flow fields were phase-locked averaged to remove the random components.